The effect of grazing exclusion on vegetation characteristics and plant community structure in arid lowland pastures - Hassan S.; Ates S.; Kaabneh A.; Louhaichi M. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Rangelands are the mainstay of pastoral livelihoods worldwide. Within rangelands, there are landscape depressions or lowlands characterized by high production potentials with their unique edaphic and hydrologic properties. The purpose of this ongoing research is to evaluate the effect of grazing exclusion on the vegetation characteristics and plant community structure in the arid lowland pastoral ecosystems. Plots were randomly identified within two distinct lowlands in Majidya and Sabha, in the Jordanian Badia. Preliminary results indicate that the total biomass and plant density widely differed between the open grazed and protected areas (P<0.001) in both sites. Total annual dry matter production was 954 kg ha-1 for protected and 151 kg ha-1 for open grazed areas in Majidya and 1749 kg ha-1 for protected and 20 kg ha-1 for open grazed areas in Sabha. The average plant densities in open grazed areas were 29 and 16 plants/m2, compared to 83 and 612 plants/m2 in protected areas in Majidya and Sabha, respectively. These results indicate that plant community structure is greatly affected by livestock grazing and that a site’s ability to recover from disturbance over time may be limited. Therefore, carefully planned grazing management is needed to achieve greater rangeland productivity and diversity.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)